Use of an active fixation lead and a subpectoral pacemaker pocket may not avoid Twiddler's syndrome - Floris E A Udink ten Cate; Roland Adelmann; Beate E Schmidt; Narayanswami Sreeram (Wolters Kluwer Medknow Publications, 2012)
Manipulation of a pacemaker with consequent malfunction of the device has been called Twiddler's syndrome. Use of active-fixation leads and subpectoral pacemaker pockets has been considered to help in avoiding this problem. We describe a child in whom twiddling was not prevented despite implantation of a lumenless atrial lead and insertion of the pacemaker generator in a subpectoral pocket.